Progam Pelatihan Budidaya Jamur Merang Melalui Media Tandan Kosong Kelapa Sawit Pada Jamaah Nahdliyin di Desa Jati Datar Lampung Tengah (Bulletin of Community Engagement, 2021)
Community empowerment in improving the standard of living was essential. As in Jati Datar Village, Bandar Mataram Subdistrict, Central Lampung Regency, the majority of which work in gardening or farming. The purpose of this assistance was to increase community independence in cultivating mushroom so that it can help the community's economy by utilizing empty oil palm bunches which is used as a medium for edible mushrooms. This research used ABCD (Asset Based Community Development) method. The results of this activity indicate that the mushroom cultivation activity has enormous potential for the community to increase economic growth. This assistance improves the economy and welfare of the community to become better than before. Keywords: Mushroom Cultivation, Mushroom Cultivation Training, JamaahNahdliyin